Brazil nut organic substrate as a viable alternative for rooting in purple joyweed (Alternanthera brasiliana) cuttings - Ferreira, A. Balbino; Mota, B. Barbosa; do Nascimento, M. Matos; de Oliveira, J. Bosco; de Lima, M. Santos; Ming, L. C. [UNESP]; Lütken, H.; Favero, B. Trevenzoli (International Society for Horticultural Science (ISHS), 2025)
Purple joyweed, Alternanthera brasiliana (L.) Kuntze is a plant belonging to Amaranthaceae, native to Brazil, and widely used in traditional medicine. In this species, seed maturation occurs non-uniformly rendering seedling production impractical. Hence, the objective of this work was to evaluate the rooting of cuttings in five substrates and three environmental conditions to optimize the propagation of joyweed. The substrate treatments considered coconut fiber (CF), decomposed Brazil nutshell (BN), organic compost (OC), commercial substrate (CS), and vermiculite (V). Cultivation environments (E) were split into intermittent misting (IF-E1), 50% shade nursery (SN-E2), and greenhouse (G-E3). The survival and rooting of the cuttings were significantly higher (p≤0.05) when BN was associated with G-E3 and CS associated with IF-E1 and SN-E2 environments, reaching 100±0.02% efficiency, when compared to all other environment x substrate combinations. There was no statistical difference in the interaction substrate × environment for final cutting height, number of leaves and side branches. When comparing the environments, the IF-E1 presented the best performance for the final cutting height (6.8±0.5 cm) and number of leaves (11.8±0.4). For the parameters fresh root mass, shoot and root dry mass a substrate × environment statistically significant interaction was found. The shoot fresh weight was best for IF-E1 combined with BN (3.1±02) and OC (3.3±0.1). Moreover, root fresh weight was superior in the combination IF-E1 × OC, i.e., 0.65±0.1 g, while root dry weight had the highest average for G-E3 × BN (99±14 mg) followed by SN-E2 × OC (86±19 mg) and IF-E1 × OC (59±14 mg). In terms of shoot dry weight, the substrate x factor did not show statistical significance, thus OC with 260±20 mg was the best substrate, and IF-E1 with 160±20 mg was the best environment. Chlorophyll a, b, and total were separately assessed between substrates and environments as no interaction between these factors was observed. The OC showed increased accumulation in all three chlorophyll analyses compared to the other substrates, while IF-E1 showed higher chlorophyll a and total compared to the other environments. It can be concluded that associating BN with G-E3 or OC and CS with IF-E1 provided better cutting survival and rooting for A. brasiliana in terms of final cutting height, and fresh and dry matter accumulation. Based on the good performance of BN, it can be a good substitute in the Amazon region and should therefore be explored as a by-product source.
Keywords: cutting; organic cultivation; penicillin; traditional medicine